KONFLIKTUSMEGELŐZÉS ÉS PREVENTÍV DIPLOMÁCIA AZ ENSZ AGENDA 30 KERETRENDSZERÉBEN - Sára, Gibárti (POLARITIES, 2020)
Ramcharan, B. – Ramcharan, R. (2020): Conflict Prevention in the UN’s Agenda 30 – Development, Peace, Justice and Human Rights, Springer.